Gold plasmon-induced photocatalytic dehydrogenative coupling of methane to ethane on polar oxide surfaces. Issue 2 (15th January 2018) - Meng, Lingshu; Chen, Zhenye; Ma, Zhiyun; He, Sha; Hou, Yidong; Li, Hao-Hong; Yuan, Rusheng; Huang, Xi-He; Wang, Xuxu; Wang, Xinchen; Long, Jinlin
Abstract : Au-Plasmon-induced resonance energy transfer modulates the charge carrier energetics of ZnO nanosheets to trigger the stoichiometric conversion of methane into ethane and hydrogen. Abstract : This work shows the solar-driven dehydrogenative coupling of methane to ethane at room temperature. A solar-to-C2 H6 energy conversion efficiency of 0.08% was achieved on the polar surface of Au/ZnO porous nanosheets (NSs), where methane C–H bonds are polarized and dissociated by the local electric field normal to the polar 001 plane, and finally converted into ethane and hydrogen through a radical coupling pathway. Mechanistic studies suggest that the Au-plasmon-induced resonance energy transfer modulates charge carrier energetics to trigger the stoichiometric conversion. Hot electrons reduce protons to H2, which is the rate-determining step of methane coupling.